Neuroprotection by chronic administration of Fluoroethylnormemantine (FENM) in mouse models of Alzheimer's disease - Allison Carles; Aline Freyssin; Sarra Guehairia; Thomas Reguero; Michel Vignes; Hélène Hirbec; Gilles Rubinstenn; Tangui Maurice (Alzheimer’s Research & Therapy)
Abstract Background Fluoroethylnormemantine (FENM), a new Memantine (MEM) derivative, prevented amyloid-β[25–35] peptide (Aβ25–35)-induced neurotoxicity in mice, a pharmacological model of Alzheimer's disease (AD) with high predictive value for drug discovery. Here, as drug infusion is likely to better reflect drug bioavailability due to the interspecies pharmacokinetics variation, we analyzed the efficacy of FENM after chronic subcutaneous (SC) infusion, in comparison with IP injections in two AD mouse models, Aβ25–35-injected mice and the transgenic APPswe/PSEN1∂E9 (APP/PS1) line. Methods In Aβ25–35-treated mice, FENM was infused at 0.03–0.3 mg/kg/day during one week after Aβ25–35 injection. For comparison, FENM and MEM were administered IP daily at 0.03–0.3 mg/kg. In 10-month-old APP/PS1 mice, FENM was administered during four weeks by daily IP injections at 0.3 mg/kg or chronic SC infusion at 0.1 mg/kg/day. Memory deficits, spatial working memory and recognition memory, were analysed. Markers of neuroinflammation, apoptosis, oxidative stress, and amyloid burden in APP/PS1 mice, were quantified. Markers of synaptic plasticity such as PSD-95 and GluN2A/B/D subunits expression in hippocampus homogenates or synaptosomes were quantified in Aβ25–35-treated mice and synaptic long-term potentiation (LTP) in hippocampal slices was analysed in APP/PS1 mice. Results Deficits in spontaneous alternation and object recognition in Aβ25–35 mice were prevented by infused FENM at all doses tested. Similar effects were observed with the daily FENM or MEM treatments. Animals infused with 0.1 mg/kg/day FENM showed prevention of Aβ25–35-induced neuroinflammation, oxidative stress and apoptosis. FENM infusion restored Aβ25–35-induced alterations in synaptosomal PSD-95, GluN2A and P-GluN2B levels. GluN2D levels were unchanged whatever the treatment. In APP/PS1 mice, FENM infused or administered IP alleviated spontaneous alternation deficits, neuroinflammation, increases in Aβ1-40/Aβ1-42 and hippocampal LTP alteration. Conclusion These data confirmed the neuroprotective potential of FENM in the pharmacological Aβ25–35 and transgenic APP/PS1 mouse models of AD, with a superiority to MEM, and showed that the drug can be efficiently infused chronically.